Diagnostic accuracy and interobserver agreement of contrast-enhanced ultrasound in the evaluation of residual lesions after treatment for malignant lymphoma and testicular cancer: a retrospective pilot study in 52 patients*. Issue 11 (2nd November 2018) - Peil-Grun, Anke; Trenker, Corinna; Görg, Konrad; Neesse, Albrecht; Haasenritter, Jörg; Görg, Christian
Abstract: Value of contrast-enhanced-ultrasound (CEUS) in the evaluation of residual lesions (RL) after therapy in patients with malignant lymphomas (ML) and testicular cancer (TC) with regard to tumor activity. From May 2004-October 2010, in n  = 52 patients with ML ( n  = 34) or TC ( n  = 18) and RL, B-mode-imaging and CEUS of the RL was performed. In CEUS, differentiation was made between high-enhancement (HE), low-(LE) or no-enhancement (NE) of the RL after therapy. Data were retrospectively evaluated. A positive test result (HE) was found in n  = 13 (25%); a negative test result (LE/NE) in n  = 39 (75%) patients. Sensitivity was 72.7%, specificity 87.8%, positive likelihood-ratio 5.96, negative likelihood-ratio 0.31. In the subgroup of ML a sensitivity of 80% and a specificity of 86.2% was reached. Active residual disease in ML and TC is associated with a marked enhancement, so CEUS might be helpful in the evaluation of RL, especially to exclude residual disease.